Positive demographic effects of nest surveillance campaigns to counter illegal harvest of the Bonelli's eagle in Sicily (Italy). (2nd December 2017) - Di Vittorio, M.; Rannisi, G.; Di Trapani, E.; Falci, A.; Ciaccio, A.; Rocco, M.; Giacalone, G.; Zafarana, M.; Grenci, S.; La Grua, G.; Scuderi, A.; Palazzolo, F.; et al.
Abstract: Illegal trade in wildlife has been identified as one of the main challenges to wildlife conservation. In 2010, an illegal trade‐ring trafficking in birds of prey was uncovered in Sicily (southern Italy). This illegal trade targeted the three most endangered species in Italy: Bonelli's eagle Aquila fasciata, Lanner falcon Falco biarmicus and Egyptian vulture Neophron percnopterus, all of them long‐lived territorial raptors threatened with extinction across their European distribution. Illegal harvest primarily involved young birds and eggs taken from nests. After the discovery of these activities, surveillance camps and camera traps connected to the mobile Global System for Mobile communications network were established in nine Bonelli's eagle breeding sites in which illegal harvest was reported. Surveillance activities resulted in a sharp reduction in illegal harvest that has contributed to the recent increase in population size and number of breeding pairs of Bonelli's eagle in the island. This population represents 95% of the entire Italian population and is catalogued as Critically Endangered in this country. Importantly, our results highlight the impact of illegal harvest on the population dynamics of endangered species as demonstrated by a population viability analysis. This is particularly important in the case of insular species for which demographic recovery due to immigration from other geographic areas is unlikely. Systematic patrols by forestry police authorities, a resolute application of Convention on International Trade in Endangered Species legislation via legal punishment, and the requirement of including all live captive specimens used for falconry in an obligatory DNA data bank would contribute to reducing the risk of extinction for small populations of endangered species of birds of prey. Abstract : Illegal trade in wildlife has been identified as one of the main challenges to wildlife conservation. Our results show that surveillance activities resulted in a sharp reduction in illegal harvest that has contributed to population increase of one of the most threatened European raptors. This is particularly important in the case of insular species for which demographic recovery due to immigration from other geographic areas is unlikely (Picture credit: P. López‐López).